PEMBERDAYAAN ZAKAT PRODUKTIF DALAM PENINGKATAN PENDAPATAN DAN KESEJAHTERAAN MASYARAKAT (MUSTAHIQ ZAKAT) DI KOTA PADANGSIDIMPUAN - Muhammad Arsad Nasution, Ahmad Soleh Hasibuan Nasruddin Kholil Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2021)
This paper discusses the distribution of productive zakat to improve the economy and community welfare (mustahiq zakat) in Padangsidimpuan City which is carried out by Baznas Padangsidimpuan City. The method used in this paper is a qualitative method, because this paper describes the empowerment of productive zakat in improving people's welfare (mustahiq zakat) by Baznas Padangsidimpuan City. Furthermore, from this description, we want to find an explanation of the tools used by the Padangsidimpuan City Baznas in distributing productive zakat, to improve the welfare of mustahiq. Productive zakat funds assistance to mustahiq can be said to increase their income. Mustahiq's welfare increases gradually and slowly. The average increase in mustahiq's monthly income is around 20%. This figure can be seen from the comparison before receiving productive zakat funds with after receiving the funds. However, this increase is not permanent but only applies four or five months after the zakat funds are received. After that the income began to decline like the previous income. This is due to the absence of good financial management. Too much profit is used as consumptive so that business capital is sucked in for daily needs.